Penerapan Strategi Active Learning dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI - Mujia, Yahdillah; Masnawati, Eli; Badriyah, Laila (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
The junior high school level is where students have started to feel less interested or less motivated to learn, especially in PAI subjects, therefore the author is interested in how PAI teachers apply active learning strategies in increasing students' learning motivation at Bahrul Ulum Middle School, Surabaya, where the location of this research is located. Dolly's village is said to be quite poor, then the researcher formulates a problem that needs to be researched, namely about how to implement active learning strategies and what the supporting and inhibiting factors for implementing active learning strategies. Researchers use a type of qualitative research method with an empirical approach, then the data collection method the author gets through observation, interviews, and documentation. the data sources that researchers obtained were from the school principal, several PAI teachers, several students, and school social media, such as websites and Instagram. After all the data has been collected, the next stage is the data analysis technique by means of data reduction, data presentation, and data verification, including the data validity technique by triangulation and consisting of source, technical, and time triangulation. The results of this research are that PAI teachers have implemented active learning strategies using various learning models to suit learning needs, PAI teachers also always encourage students, and in every school, there are motivational words for students. And the supporting factor is the availability of school facilities to make learning easier, then the inhibiting factor is the condition of the classrooms, which are hallways that disrupt the learning of other classes.